Original articleSphingosine kinases modulate the secretion of amyloid β precursor protein from SH-SY5Y neuroblastoma cells: the role of α-synuclein - Jesko, Henryk; Okada, Taro; Strosznajder, Robert P.; Nakamura, Shun-ichi (Folia Neuropathologica, 2014)
Sphingosine kinases (SphK 1&2) are involved in the regulation of cell survival, differentiation and neurotransmitter secretion. Current data suggest potential links between sphingolipid signalling, α-synuclein (ASN) and Alzheimer’s disease (AD). Our aim was to investigate the possible role of SphKs and ASN in the regulation of the production and secretion of the amyloid β precursor protein (APP). We have previously shown that ASN intensified the secretion and toxicity of amyloid β (Aβ) to the point where it caused cell death. Our current results show that APP, the precursor protein for Aβ, is also influenced by ASN. The stable overexpression of wtASN in SH-SY5Y cells caused a three-fold, significant increase of the cellular APP level. This suggests that the influence of ASN on Aβ metabolism may actually occur at the level of APP protein rather than only through the changes of its cleavage into Aβ. To elucidate the mechanisms of APP modulation the cells were exposed to S1P and an SphK inhibitor (SKI). 72 h S1P treatment at 5 µM caused a nearly 50% reduction of the cellular APP signal. S1P also caused a tendency towards higher APP secretion, though the results were insignificant. The inhibition of SphKs decreased medium APP levels in a dose-dependent manner, reaching significance at 5 µM SKI with a correspondingly elevated intracellular level. Thus, it is reasonable to expect that in fact the influence of SphK activity on APP might be pro-secretory. This would also be in agreement with numerous articles on SphK-dependent secretion in the literature. The chronic nature of AD further suggests that subtle alterations in APP metabolism could have the potential to drive important changes in brain condition.